1999
DOI: 10.3133/ofr99244
|View full text |Cite
|
Sign up to set email alerts
|

Ground-water quality data from the Abbotsford-Sumas aquifer of southwestern British Columbia and northwestern Washington State, February 1997

Abstract: , and minimum reporting levels, drinking water standards, and freshwater criteria for protection of aquatic life .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The ASA is an unconfined aquifer predominantly made up of glaciofluvial sand and gravel with minor till and clayey silt lenses, with depths up to 70 m (Dakin, 1993). The average water table depth is 12 to 40 m below the surface (Cox and Liebscher, 1999). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASA is an unconfined aquifer predominantly made up of glaciofluvial sand and gravel with minor till and clayey silt lenses, with depths up to 70 m (Dakin, 1993). The average water table depth is 12 to 40 m below the surface (Cox and Liebscher, 1999). …”
Section: Methodsmentioning
confidence: 99%
“…Land use on the ASA has long been predominantly agriculture (Hii et al, 1999). Red raspberry and blueberry ( Vaccinium corymbosum L.) are the dominant crops, whereas poultry broiler production is the dominant animal production on the ASA (Cox and Liebscher, 1999; Zebarth et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the maintenance of septic tanks in high residential watersheds should be considered. Management alternatives for lowering the manure loading may include dairy animal herd reduction, manure exporting, and the adoption of feeding strategies to reduce the nitrogen content in animal waste (Davis et al, 1999;Rotz et al, 1999;Jonker et al, 2002). Management alternatives related to fertilizer application include the use of nitrification inhibitors, the use of surrogate fertilizers that have lower amounts of nitrogen, split application of fertilizers, and accounting for nitrogen in the irrigation water and soil (Delgado and Mosier, 1996;Delgado, 2001b).…”
Section: Prioritization Of Management Actionsmentioning
confidence: 99%
“…The results showed that nitrate concentrations ranged from less than 0.01 to 53 mg/l. Many studies showed that agricultural practices, dairy farming, and lagoons are the probable cause of excessive nitrate levels in the shallow ground water of the area (Liebscher et al, 1992;Erickson, 1992Erickson, , 1994Garland and Erickson, 1994;Hulsman, 1998;Hii et al, 1999;Cox and Liebscher, 1999;Carey, 2002). In order to manage nitrogen pollution and other water-related issues, Washington State Legislature passed the Engrossed Substitute House Bill 2514 codified as RCW 90.82 in 1988.…”
Section: Introductionmentioning
confidence: 96%
“…Low precipitation during the crop growing season (April–September) makes the region irrigation dependent. The occurrence of the majority (∼70%) of precipitation between October to March results in a highly seasonal recharge pattern and high water table fluctuation (2 to 3 m annually, on average; Kohut, 1987; Cox and Liebscher, 1999; Graham et al, 2015). Regional groundwater flow is generally from the north, toward the Nooksack River in the south.…”
Section: Methodsmentioning
confidence: 99%